Vol. 98 : Interdisciplinary Problems of Nanotechnology, Biomedicine and Nanotoxicology (Nanobiotech 2015): 3rd International Youth Conference, 21–22 May 2015, Tambov, Russia; [proceedings]; IOP Conference Series : Materials Science and Engineering - Refsnes M. Magne; Gusev A. Alexander; Godymchuk (Godimchuk) A. Yu. Anna Yuryevna; Bogdan A. M. Anna Mikhailovna (2015, 2015)
Title screen